Dynamic compressive response of zirconium diboride‐silicon carbide composites at high‐strain rates. Issue 6 (30th May 2019) - Wang, Mi; Kong, Dewen; Wang, Lingling; Li, Youbin; Cai, Ting
Abstract: The quasi‐static, dynamic compression experiments and micromechanical model were employed to declare the dynamic compressive response of ZrB2 –20%SiC composite at high‐strain rates. The quasi‐static compressive strengths were measured to determine the range of initial microcrack length in ZrB2 –20%SiC composite. The effects of the strain rate on dynamic compressive strength, critical stain, as well as fracture mechanisms were discussed based on experimental results. Dynamic mechanical properties of ZrB2 ‐based composites display obvious strain rate dependence. The dynamic increase factor in the compressive strength shows a rapid increase above a transition strain rate of 1228 s −1 . Moreover, a micromechanical model considering initial microcrack lengths is used to predict dynamic compressive strengths, which agree with the experimental results. Additionally, the critical strain has a linear increase tendency with the increase of strain rate. The dynamic compressive fracture mechanism of ZrB2 –20%SiC composite is relative to the combination effect between strain rate and microstructure. The size of flaw distribution is critical below the transition strain rate resulting in bigger fragments, whereas the flaw density is primary with more and smaller fragments above the transition strain rate. Abstract : Effects of strain rate on mechanical response of ZrB2 ‐SiC composites.